Alpha7 Nicotinic Acetylcholine Receptors Play a Predominant Role in the Cholinergic Potentiation of N-Methyl-D-Aspartate Evoked Firing Responses of Hippocampal CA1 Pyramidal Cells - Bali, Zsolt K.; Nagy, Lili V.; Hernádi, István (Frontiers in Cellular Neuroscience, 2017)
The aim of the present study was to identify in vivo electrophysiological correlates of the interaction between cholinergic and glutamatergic neurotransmission underlying memory. Extracellular spike recordings were performed in the hippocampal CA1 region of anesthetized rats in combination with local microiontophoretic administration of N-methyl-D-aspartate (NMDA) and acetylcholine (ACh). Both NMDA and ACh increased the firing rate of the neurons. Furthermore, the simultaneous delivery of NMDA and ACh resulted in a more pronounced excitatory effect that was superadditive over the sum of the two mono-treatment effects and that was explained by cholinergic potentiation of glutamatergic neurotransmission. Next, animals were systemically treated with scopolamine or methyllycaconitine (MLA) to assess the contribution of muscarinic (mAChR) or α7 nicotinic (nAChR) receptor-mediated mechanisms to the observed effects. Scopolamine totally inhibited ACh-evoked firing, and attenuated the firing rate increase evoked by simultaneous application of NMDA and ACh. However, the superadditive nature of the combined effect was preserved. The α7 nAChR antagonist methyllycaconitine (MLA) robustly decreased the firing response to simultaneous application of NMDA and ACh, suspending their superadditive effect, without modifying the tonic firing rate increasing effect of ACh. These results provide the first in vivo electrophysiological evidence that, in the hippocampal CA1 region, α7 nAChRs contribute to pyramidal cell activity mainly through potentiation of glutamatergic signaling, while the direct cholinergic modulation of tonic firing is notably mediated by mAChRs. Furthermore, the present findings also reveal cellular physiological correlates of the interplay between cholinergic and glutamatergic agents in behavioral pharmacological models of cognitive decline.